Caracterização fenotípica de Cepas de Staphylococcus aureus isoladas de queijos ricota - Pinto, Taiz Siqueira (2011)
This study aimed to isolate strains of Staphylococcus aureus in ricotta cheeses and to characterize them respecting phenotypic markers of lipolytic activity, and bacteriocin typing and resistance typing. For isolation, were acquired 11 samples of different brands of ricotta cheese sold in supermarkets in João Pessoa - Paraíba. Among the 41 strains, 82.9% proved positive lipase (Lip+) and 17.1%, negative lipase (Lip-). In relation to bacteriocin typing, 9.76% showed bacteriocin producing against a strain of Staphylococcus aureus isolated from surfaces processing food and 55% were susceptible to a strain of Staphylococcus aureus isolated from ricotta cheese. For resistance typing, 87.8% of strains were resistant to streptomycin, 26.59% to penicillin and 19.51% to erythromycin. None of the strains were resistant to tetracycline. Variability was observed between the minimal inhibitory concentrations (MIC), both in resistant strains as sensitive ones, so the variability showed more prevalent with penicillin (ranging from 0.015625 to 16 mg / mL) and the variability between strains of the same cheese. Only erythromycin-resistant strains were subjected to "D-test" to determine the type of resistance, of which all presented inductive resistant. From this results obtained, can conclude that although the phenotypes show an adaptive answer on related to the peculiarities of local environmental pressures, it is clear the importance of these genetic markers to discern new strains of S. aureus for those endemic, as well as to investigate possible epidemiological impacts and on food safety.